Origin of dark mass apparentfrom gravitationally bound extended ordinary material systems - Biswas, Shubhen (International Journal of Advanced Astronomy, 2016)
To grow up a gravitationally bound system with fixed proper mass requires sufficient energy to overcome the gravitational pull. Following General relativity both matter energy and field energy act on the source of gravity. Apart from the field energy if our concern is just for the bound system of mass only, then we can easily attribute the gain of matter energy as the gain of gravitational mass. This gain of matter energy can be backed immediately if the system is allowed to collapse to its initial state. So in the case of expansion there will be no possibility in creation of normal or proper mass. But the concern regarding the gain of matter energy must have realistic effect in increase of gravitational mass. This article explains how gravitational mass of the gravitationally bound large material system like galaxy exceeds its ordinary mass with the size of the system. Here presence of the dark mass and flat rotation curveÂ are given without considering MOND theory, not even distorting any accepted paradigm of post Newtonian gravity. The findings are truly consistent with the recent observed data.